2022
DOI: 10.3390/pharmaceutics14030539
|View full text |Cite
|
Sign up to set email alerts
|

How Long Do Implanted Triclosan Sutures Inhibit Staphylococcus aureus in Surgical Conditions? A Pharmacological Model

Abstract: (1) Background: Sutures with triclosan (TS) are used to reduce the risk of surgical site infections (SSI), but most clinical trials are inconclusive. The traceability of SSI risk to antimicrobial activity in operated tissues is needed. (2) Objectives: This study aimed to predict triclosan antistaphylococcal activity in operated tissues. (3) Methods: Three TS were exposed to static water for 30 days, and triclosan release was recorded. Polyglactin TS explanted from sheep seven days after cardiac surgery accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…V, P, M and triclosan-resistant P. aeruginosa were the controls. The experimental settings were the same as those used in static water release kinetics [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…V, P, M and triclosan-resistant P. aeruginosa were the controls. The experimental settings were the same as those used in static water release kinetics [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its dissolution rate is slow around the suture, whose volume is 0.3 to 0.4% of the culture volume. Therefore, unless the tube is shaken, the triclosan diffusion layer forms a gradient with a maximum close to 10 µg/mL at the suture surface, decreasing with the distance from the source [ 7 , 26 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Triclosan is a broad-spectrum antimicrobial, and in vitro and animal studies have shown that it inhibits microbial colonisation in TSs [ 16 , 17 , 18 , 19 , 20 , 21 ]. Once implanted, TSs are estimated to display biocidal-level antistaphylococcal activity during the first 4 to 12 h [ 22 ]. Therefore, TSs potentially reduce SSI development through the early decrease in bacterial load at the suture surface and the inhibition of suture colonisation.…”
Section: Introductionmentioning
confidence: 99%